Inveterate luxation of Monteggia. Modified Bell-Tawse technique - Cáceres Sánchez, Libertad; Farrington, David M. (Revista Colombiana de Ortopedia y Traumatología, 2016)
Monteggia’s injury is a fracture of the proximal ulna which is associated with anterior dislocation of the proximal radioulnar joint. It is not a common injury in children (it only represents 2% of fractures of the elbow) and inveterate cases are even more unusual. Many surgical treatments have been proposed for this injury. Nevertheless, there is not a general agreement regarding the necessity of the annular ligament reconstruction. Here we describe the modified technique of Bell-Tawse in a 5 and a half year patient with inveterate Monteggia injury.